Outcome of surgical treatment of highgrade intramedullary astrocytomas - Flamerz, Bassam M. (AL-Kindy College Medical Journal, 2011)
Background: Intramedullary astrocytomasaccount for about 1% of all CNS tumors and6–8% of spinal cord tumors. The vast majorityof intramedullary astrocytomas are slowgrowinglesions.Objectives: The goal in this study was toreview a series of patients who underwentsurgical removal of intramedullary high-gradeastrocytomas, focusing on the functionaloutcome and the effect of multimodalitytreatment on the survival of patients with highgrade intramedullary astrocytoma.Methods: Between June 1999 and June 2004,22 patients underwent removal ofintramedullary high-grade astrocytomas in fourneurosurgical hospital in Baghdad/ Iraq(Neurosurgical hospital, Al Shaheed AdnanHospital for Surgical Speeialticsa, NursingHome Hospital Lesions were located in thecervical segment of the spinal cord in 12patients, and patients.Results: Histological examinations showed10 Grade III astrocytomas and 12glioblastomas. Only 2 of the 22 high-gradeastrocytomas could be completely removed. Theclinical postoperative status worsened in14 patients (63.6%), was unchanged in sevenpatients (31.8%), and there was one case ofintraoperative death (4.5%). None of the 22patients showed improvement in theirneurological status postoperatively. In this series,excluding the one intra-operative death, allpatients died of the progression of themalignancy.Conclusions: Surgical treatment did notameliorate the postoperative neurological status;instead, in the majority of cases, it prompted aworsening of the deficit. Radiotherapy andchemotherapy have a little influence on thelength of survival. In this series, multimodalitytreatment of intramedullary high-gradeastrocytomas has been shown to increase lengthof survival without improving the neurologicalstatus.